Assessing community information literacy through the empowering eight model: Evidence from Rumah Peradaban SNC Fannaz Indonesia - Karauna, Yusrin; Sunyianto, Sunyianto; Fadli, Mohammad; Nurainun, Seri (Priviet Social Sciences Journal, 2025)
This study analyzes the information literacy skills of the community based on the Empowering Eight model at the SNC Fannaz civilization house in Sei Mencirim Village, Deli Serdang Regency. The aim was to determine the community's literacy skills based on the Empowering Eight model. The method used was a survey and questionnaire with descriptive statistical data analyses. The results of the study showed that based on the calculations of the Grand Meanon eight model indicators of Empowering Eight (E8), the information literacy skills of the members of the SNC Fannaz Civilization House showed very optimal achievements and were in the very high category for all aspects. Mastery of the Search and Assessment Stages (Identify, Explore, Select, Access): The four indicators with the highest average values ​​(3.49 - 3.58) are Explore (3,49), Select (3,58), Present (3.54), and Access (3.50). This shows that members have a very strong ability to seek information from various sources (Explore), select and evaluate the most relevant information (Select and Access), and effectively present their findings (Present). The achievement of the management and utilization stages (Organize, Create, Apply) was measured by the indicators Organize (3,36), Apply (3.27), and Create (3.11). Although Create (3.11) is the lowest value among all indicators, it is still in the very-high category. This shows that the ability of members to create new information products from existing sources is the aspect that needs the most improvement, but fundamentally, it is still very good.